Transitivity Process in Mary Norton’s Novel the Borrowers (1952) - Yulia Rendadirza; Havid Ardi (English Language and Literature, 2020)
This study analyzed the transitivity process in the novel The Borrowers. The method used in this research was descriptive qualitative.This study focused on transitivity which is a part of the Ideational meaning in Systemic Functional Linguistics (SFL).According to Halliday, the three main components in transitivity are the process itself, the participants involved in the process and circumstance. There are six process of transitivity, namely Material, Mental, Relational, Behavioral, Verbal and Existential. The data in this study were divided into two, which were utterances and narrations. This study only focused on chapter one. The source of data in this research wasa novel The Borrowers written by Mary Norton. This study aims to find out the dominant process found in the novel. The instrument used was the researcher herself and assisted by the analysis tableto show the dominant process found in the novel.In analyzing the data, the researcher used several steps, which were reading the text, identify the data and put it in data card, calculated the data, and making conclusion.There are 269 clauses of transitivity found in the chapter one of the novel The Borrowers. The process that appears mostly in chapter is Relational: Attributive with 67 clauses/ 24.90%. Research on transitivity has been done a lot before. Nonetheles, there is a difference between between the new research and the old one. Other researchers who also examined transitivity in fiction text were (Kurnia, 2018; Koutchade, 2017; Rashid, 2016). Most researchers in fiction text only examined short story, and the data results that obtained are all the clause of the full story. However, this research only focuses on the beginning chapter in fiction text.